Answer:
from least to greatest 112 121 124 137 147 156 173 189
Step-by-step explanation:
if you subtract each number from a number that is greater than all the numbers for example 200 then what ever has the most left will be greatest and least will be least for example 121 - 200 is negative 79 and 189 - 200 is negative 11 negative 11 is higher so its a greater number there is also easier ways to do this but this is just extra
Answer:
Yes, the shapes are similar. Note, the angles are equivalent and the sides are scales of each other satisfying the requirements for similarly.
Step-by-step explanation:
For a shape to be similar there are two conditions that must be met. (1) Must have equivalent angles (2) Sides must be related by a scalar.
In the two triangles presented, the first condition is met since each triangle has three angles, 90-53-37.
To test if the sides are scalar, each side must be related to a corresponding side of the other triangle with the same scalar.
9/6 = 3/2
12/8 = 3/2
15/10 = 3/2
Alternatively:
6/9 = 2/3
8/12 = 2/3
10/15 = 2/3
Since the relationship of the sides is the scalar 3/2 (Alternatively 2/3), then we can say the triangles meet the second condition.
Given that both conditions are satisfied, then we can say these triangles are similar.
Note, this is a "special case" right triangle commonly referred to as a 3-4-5 right triangle.
Cheers.
I don't have my glasss on and there are too many 1's which are messing with my eyes but all i have to say is PEMDAS
bonus question - i used to like school but at this point i just want to graduate
Answer:
in a monthly shy much $3500
in a weekly she much $807.69
Step-by-step explanation:
Consider the following functions. f={(−4,−1),(1,1),(−3,−2),(−5,2)} and g={(1,1),(2,−3),(3,−1)}: Find (f−g)(1).
fenix001 [56]
Answer:
0
Step-by-step explanation:
Subtraction of functions has the property:
f={(−4,−1),(1,1),(−3,−2),(−5,2)} has (1,1) means that f maps 1 to 1, therefore f(1) = 1
g={(1,1),(2,−3),(3,−1)} has (1,1), means that g maps 1 to 1, therefore g(1)=1
As a Result, since (f−g)(1) = f(1) - g(1), we have (f−g)(1) = 1-1=0